STRENGTHENING FAMILIES IN THE DIGITAL ERA: A DIGITAL LIFE BALANCE PROGRAM HELD IN GADUT KANAGARIAN, TILATANG KAMANG SUB-DISTRICT, AGAM DISTRICT - Fikry, Zulian; Sari, Putri Minas; Putra, Yanladila Yeltas; Rizal, Gumi Langerya; Aprisi, Sherly; Termizal, Maharani Tosca; Elvika, Rahma Rezki (LPPM Univ. Ibn Khaldun Bogor, 2024)
The community service program titled